2004
DOI: 10.1515/znc-2004-7-803
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Immunomodulatory Constituents of Henna Leaves

Abstract: The immunomodulatory bioassay-guided fractionation of the methanolic extract of henna (Lawsonia inermis L.; syn. Lawsonia alba L.) leaves resulted in the isolation of seven compounds; three have been isolated for the first time from the genus, namely p-coumaric acid, 2-methoxy-3-methyl-1,4-naphthoquinone and apiin, along with the previously isolated compounds: lawsone, apigenin, luteolin, and cosmosiin. Structural elucidation of the isolated compounds was based upon their physical, chemical as well as spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 4 publications
2
76
0
Order By: Relevance
“…All the above immune indices, however, were found to be affected in a time and dose-dependent manner. Previously, in vitro studies revealed that the methanolic extract of L. inermis displayed immunostimulatory effect as indicated by an enhanced macrophage-stimulating activity and promotion of T-lymphocyte proliferative responses in human (Wagner et al 1988;Mikhaeil et al 2004). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the above immune indices, however, were found to be affected in a time and dose-dependent manner. Previously, in vitro studies revealed that the methanolic extract of L. inermis displayed immunostimulatory effect as indicated by an enhanced macrophage-stimulating activity and promotion of T-lymphocyte proliferative responses in human (Wagner et al 1988;Mikhaeil et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, L. inermis has also been used in ethno-medicine to treat various maladies including arthritis, headaches, ulcers, diarrhea, leprosy, intestinal neo-plasticity, jaundice, fever, leucorrhoea, diabetes, and small pox (Elmanama et al 2011). In addition, in vitro immunomodulatory properties of henna leaves have also been reported (Dikshit et al 2000;Mikhaeil et al 2004). More recently, the methanolic extract of L. inermis has been shown to exert an immunomadilatory effect in striped murrels (Channa striatus) (Uthayakumar et al 2014a).…”
Section: Introductionmentioning
confidence: 95%
“…In fact, these compounds acted, in particular, as good proton donors reacting with free radicals to convert them to more stable products and terminate the radical chain reaction. Many researchers have shown the antioxidant activities of leaves henna extracts [6,30,31]. Mikaehil et al [31] have indicated that henna leaves are rich in Lawsone, apigenin, luteolin, cosmosiin, p-coumaric acid, 2-methoxy-3-methyl-1,4-naphthoquinone and apiin, which are considered as excellent antioxidant compounds.…”
Section: In Vitro Antioxidant Activity Of Ahe Csg-gels and Csg-filmsmentioning
confidence: 99%
“…In India, it is cultivated as cash crop particularly in Sojat area of Pali district, Rajasthan (Chand and Jangid 2007). Many pharmacological studies revealed that Henna has been reported to have analgesic, hypoglycemic, hepatoprotective, immunostimulant, antiinflammatory, antibacterial, antimicrobial, antifungal, antiviral, antiparasitic, antitrypanosomal, antidermatophytic, antioxidant, antifertility, tuberculostatic and anticancer properties (Mikhaeil et al 2004;Syamsudin and Winarno 2008;Chaudhary et al 2010). L. inermis is also well known for its use as cosmetic for staining hair and hands and popular among women/girls who use it for beautifying their hands and feet in an artistic way during auspicious occasion like wedding and festivals.…”
Section: Introductionmentioning
confidence: 99%